A retrospective study of PBDEs and PCBs in human milk from the Faroe Islands - Grandjean Philippe; Strid Anna; Fängström Britta; Weihe Pál; Bergman Åke (BMC, 2005)
Abstract Background Persistent organic pollutants (POPs) in wildlife and humans remain a cause of global concern, both in regard to traditional POPs, such as the polychlorinated biphenyls (PCBs), and emerging POPs, such as the polybrominated diphenyl ethers (PBDEs). To determine the time related concentrations, we analyzed human milk for these substances at three time points between 1987 and 1999. Polychlorobiphenylols (OH-PCBs), the dominating class of PCB metabolites, some of which are known to be strongly retained in human blood, were also included in the assessment. Methods We obtained milk from the Faroe Islands, where the population is exposed to POPs from their traditional diet (which may include pilot whale blubber). In addition to three pools, nine individual samples from the last time point were also analyzed. After cleanup, partitioning of neutral and acidic compounds, and separation of chemical classes, the analyses were carried out by gas chromatography and/or gas chromatography/mass spectrometry. Results Compared to other European populations, the human milk had high PCB concentrations, with pool concentrations of 2300 ng/g fat 1987, 1600 ng/g fat in 1994, and 1800 ng/g fat in 1999 (based on the sum of eleven major PCB congeners). The nine individual samples showed great variation in PCB concentrations. The OH-PCBs were present in trace amounts only, at levels of approximately 1% of the PCB concentrations. The PBDE concentrations showed a clear increase over time, and their concentrations in human milk from 1999 are among the highest reported so far from Europe, with results of individual samples ranging from 4.7 to 13 ng/g fat Conclusion Although remote from pollution sources, the Faroe Islands show high concentrations of POPs in human milk, particularly PCBs, but also PBDEs. The PBDEs show increasing concentrations over time. The OH-PCB metabolites are poorly transferred to human milk, which likely is related to their acidic character.